2010
DOI: 10.1016/j.nlm.2009.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Memory-enhancing corticosterone treatment increases amygdala norepinephrine and Arc protein expression in hippocampal synaptic fractions

Abstract: Considerable evidence indicates that glucocorticoid hormones enhance the consolidation of memory for emotionally arousing events through interactions with the noradrenergic system of the basolateral complex of the amygdala (BLA). We previously reported that intra-BLA administration of a β-adrenoceptor agonist immediately after inhibitory avoidance training enhanced memory consolidation and increased hippocampal expression of the protein product of the immediate early gene activity-regulated cytoskeletal-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 61 publications
4
83
1
Order By: Relevance
“…Indeed, all discrimination measures of the 3 rd familiarization session were higher compared to any of other individual sessions except the 4 th . Many studies have shown that stress can have varying effects on memory functioning [50][51][52][53][54][55]. Memory can be facilitated when stress is experienced in the same context and around the time of learning [56].…”
Section: Familiarizationmentioning
confidence: 99%
“…Indeed, all discrimination measures of the 3 rd familiarization session were higher compared to any of other individual sessions except the 4 th . Many studies have shown that stress can have varying effects on memory functioning [50][51][52][53][54][55]. Memory can be facilitated when stress is experienced in the same context and around the time of learning [56].…”
Section: Familiarizationmentioning
confidence: 99%
“…However, it is not understood how GCs interact with the noradrenergic system in influencing memory retrieval, because these effects seem to be too rapid to act through the classical genomic mode of action of GCs (6,10,11,[20][21][22][23]. Findings of recent studies investigating the cellular mechanism underlying the rapid effects of GCs suggest a possible involvement of the endocannabinoid system (24-27).…”
mentioning
confidence: 99%
“…Other findings in our laboratory have shown that training conditions that evoke emotional arousal (e.g. footshock stimulation) or direct injection of epinephrine or corticosterone in doses that facilitate memory significantly increases NE release in the amygdala and this effect is directly related to the stimulus intensity [92][93][94][95][96].…”
Section: The Noradrenergic System Of the Amygdala Is Involved In Modumentioning
confidence: 71%
“…Interestingly, it has been shown that the relative severity of the stressor and its physiologic impact can vary between individuals [93]. Thus, the severity of stress produced by a stimulus, whether physiologic or psychogenic, has typically been defined in terms of the magnitude of the physiological response it elicits, e.g., by measuring activation of the hormonal hypothalamic-pituitary-adrenal (HPA) stress axis or of the peripheral sympathoadrenal autonomic response system.…”
Section: The Noradrenergic System Of the Amygdala Is Involved In Modumentioning
confidence: 99%